An estimated contribution of glacier runoff to Mongolia's Upper Khovd River Basin in the Altai Mountains - Pan, Caleb G.; Kamp, Ulrich; Munkhjargal, Munkhdavaa; Halvorson, Sarah J.; Dashtseren, Avirmed; Walther, Michael (Mountain research and development, 2019)
In the semiarid climate of northwestern Mongolia, glaciers are critical contributors to water resources, particularly during the dry summer months. Nevertheless, our knowledge of the contribution of glacier runoff in the Upper Khovd River Basin (UKRB) is limited. This study investigates the impact of glacier recession on the UKRB's hydrology in western Mongolia's Altai Mountains. The analysis included glaciological method measurements, satellite-derived glacier extent records, and a simple ice ablation model. Our modeling used a mass balance gradient of 0.50 meters water equivalent 100 m-1 for the years 2000, 2010, and 2016 and included a sensitivity analysis that applied lower and upper mass balance gradient values and ±200 m around the equilibrium line altitude (ELA). The glacier contribution to the UKRB's water resources decreased from almost 8% in 2000 to 6.7% in 2016. Hypsometries revealed that glacier areas decreased at all elevations, indicating that only small accumulation zones exist. Therefore, applying a modeled increased ELA better represents glacier contribution to total runoff, at 18.7% in 2000 and 15.4% in 2016. The decreasing glacier runoff contribution indicates that the UKRB glaciers have passed the tipping point of an increased contribution that first follows enhanced melting. The continued glacier recession and uncertain water availability represent challenges for water resource management and future human-water relations in the Mongolian Altai.